Meningkatkan Kompetensi dan Kepercayaan Diri dalam Menyusun Tugas Akhir Melalui Pelatihan Penulisan Skripsi - Amirya, Mirna; Arisanti, Nadya; Setyowati, Eka Yuli (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Thesis Writing Training for Semester 6 Students of the IAIN Kediri Sharia Accounting Study Program aim to increase students' competency and confidence in writing theses. This activity uses the service learning method with a lecture approach, which is effective in conveying information and allows direct interaction between the presenter and participants. The training was held for two days, including an explanation of thesis structure, research methodology, and the application of sharia principles in accounting research. The evaluation of the activities showed that the majority of students felt helped and more confident in facing the thesis writing process. Active interaction during lecture sessions and group discussions provides practical solutions to problems faced by students and increases their motivation. Thus, this training was successful in supporting students in achieving optimal academic achievement in accordance with applicable academic standards.